Patterns of scald injuries. Issue 2 (August 1994) - Yeoh, C; Nixon, J W; Dickson, W; Kemp, A; Sibert, J R
Abstract : OBJECTIVES–To describe common patterns of bath water scald injuries in children, to examine differences between accidental and non-accidental bath water scalds in children, and to examine potential for prevention. DESIGN–A two year six month retrospective analysis of admissions to a specialist burns unit. SETTING–The Burns Unit, St Lawrence Hospital, Chepstow serving children from south and west Wales. SUBJECTS–Sixty eight children attending the Burns Unit for treatment of bath related scald injuries. RESULTS–Bath scalds in children under 5 years of age was the cause of 14.7 per 100, 000 children being admitted to the specialist burns unit in a year. The majority of the children were injured by falling in the bath but the tap was turned on by seven children themselves and by 10 siblings. Six children put hands in the hot water and two children were accidentally put into bath water that was too hot and were quickly withdrawn. Four children suffered probably non-accidental immersion scald injuries from hot water. They were characterised by a clear tide mark, a story that did not fit the injuries, associated injuries, and by symmetrical lesions. Accidental scalds were irregular geographical injuries and were asymmetrical. CONCLUSIONS–Bath scalds are a significant problem in children under 5 years. Their prevention should be part of an injury control programme on a local and national level. The best way to achieve this would be by reducing the temperature in domestic hot water tanks. The recognition of non-accidental bath scalds can be assisted by the pointers outlined and should be done in a multidisciplinary way with plastic surgeons, paediatricians, and social workers working together.